Philosophy of Art as Meta-Criticism: Some Questions after Noël Carroll - Pucciarelli, Daniel (Discurso, 2023)
The article inquires the recent revitalization of philosophy of art as meta-criticism, by Noël Carroll. It will particularly examine the normative content of Carrollian meta-criticism as it is revealed in his concept of art criticism and in his doctrine of critical evaluation. The hypothesis defended in the article is that Carroll raises transitory configurations of the artworld and the ontology of the artwork to the condition of critical norm, which contributes to the fact that his meta-criticism becomes an abstract theory of art criticism. However, we can deduce from Carroll’s account valuable indications for a contemporary reform of art meta-criticism.